Synopsis: The Sustainable Land Management Program in the Ethiopian highlands: An evaluation of its impact on crop production - Schmidt, Emily; Tadesse, Fanaye (International Food Policy Research Institute, 2017)
Agricultural productivity in Ethiopia’s highlands, the country’s breadbasket, is threatened by severe land degradation. To mitigate ongoing soil erosion and soil nutrient loss, the government of Ethiopia initiated the Sustainable Land Management Program (SLMP). We evaluated the program’s impact on the value of agricultural production in select kebeles (administrative sub-districts) in which it was implemented using a two-round survey of farm households.